IMPLEMENTATION OF MINIMUM SERVICE STANDARD IN JEMBRANA REGENCY AS AN EFFORT TO CREATE ACCOUNTABLE REGIONAL GOVERNMENT A MODEL FOR THE GOVERNMENT OF PEMATANGSIANTAR REGENCY - Edward Simon Hasudungan Sitorus (Pusbindiklat - LIPI, 2012)
This writing is trying to analyze the Implementation Minimum Standard of Service particularly in PermittanceService related to create the accountable Jembrana Local Government. In order to reach the purpose, thisstudy is using qualitative method by observing the secondary data from various resources. This study shows thatJembrana Local Government is successful to implement Minimum Standard of Service particularly in PermittanceService through procedure assurance, time assurance and cost assurance. The implementation has the effect inincreasing indigenous region income, number of trader, employment and investment. The effects then, will createaccountable local government. Furthermore, Pematangsiantar Local Government can make this model to beimplemented in its region.